Modeling and stability analysis for an ultrasonic motor - Gutshchmidt, Stefanie; Seplsberg-Korspeter, Gottfred; Hagedorn, Peter (Vietnam Journal of Mechanics, 2007)
The development of motor models, adequate for motor design and optimization is still behind the technological state of the art. The reason for this lies in the fact that a couple of years ago the main emphasis regarding ultrasonic motors was on finding new principles or prototypes while today this has shifted towards optimization of known working concepts and motors. A systematic motor optimization demands, among at her things, a detailed dynamical understanding of the motor which not too often exists for ultrasonic motors in general. The present study deals with modeling a wobbling disk piezoelectric motor. For the model the analytic steady state solution is derived and stability of the solution is investigated. The model and the analytic steady state solution yield a detailed insight in essential dynamical phenomena by which the motor is driven. The model framework may be a guideline providing understanding in the working principle, dynamics, weighting of the parameters with respect to reliable, stable operation and optimization of such motors.